Peningkatan Kesejahteraan Mansyarakat Melalui Kegiatan Pembinaan UMKM Makanan Ringan Di Wilayah Tangerang - Silaswara, Diana; Parameswari, Rinintha; Kusnawan, Agus; Anggraeni, Dian; Ginny, Puti Lenggo (LP3kM Universitas Buddhi Dharma, 2021)
This activity is hold to Maximize and motivate the society of Tangerang city businessman of MSME. However the development is used to give solution of capital, marketing, product design and legality and motivation. The purpose of this training is to improve MSME Management Management, which is expected to increase its business in marketing products and using E-Commerce optimally.In this training, the on the spot method to the business field is used, the method of observation, discussion, and experience of the trainer and condition now days. The method of discussion and question and answer, as well as the provision of materials and practices for improving business planning management marketing management management (E- Commerce). Several participants were also asked to explain the results of their business plans. The hope is that the results of the evaluation of 30 training participants generally show an increase in knowledge and understanding after being given Marketing and E-commerce materials to improve the management of MSME management in Tangerang City